Jumping spiders from Ivory Coast collected by J.-C. Ledoux (Araneae, Salticidae) - Wesołowska, Wanda; Russell-Smith, Anthony (European Journal of Taxonomy, 2022)
This paper contains the results of research on a large assemblage of jumping spiders collected by J.-C. Ledoux from Ivory Coast in 1974–75. In total, 105 species are included. Three new genera are erected Pulcherula gen. nov., Sphericula gen. nov. and Vicirionessa gen. nov. Two generic names are synonymized, Polemus Simon, 1902 with Baryphas Simon, 1902 and Brancus Simon, 1902 with Thyene Simon, 1885. Twenty eight new species are described: Afraflacilla albopunctata sp. nov. (♀), Ansienulina lamottei sp. nov. (♂), Asemonaea pusilla sp. nov. (♀), Detalik cavally sp. nov. (♀), Evarcha zougoussi sp. nov. (♀), Heliophanus (Heliophanus) minimus sp. nov. (♂♀), Hyllus ignotus sp. nov. (♀), Hyllus solus sp. nov. (♀), Hyllus unicolor sp. nov. (♀), Icius bandama sp. nov. (♂♀), Langona recta sp. nov. (♂), Malizna zabkai sp. nov. (♀), Menemerus niangbo sp. nov. (♀), Myrmarachne galea sp. nov. (♀), Phintella brevis sp. nov. (♂), Phintella globosa sp. nov. (♀), Phintella occidentalis sp. nov. (♂), Phintella transversa sp. nov. (♂), Pochytoides mirabilis sp. nov. (♂♀), Pochytoides tonkoui sp. nov. (♀), Pochytoides tournieri sp. nov. (♂), Pulcherula magna gen. et sp. nov. (♂), Rhene ferkensis sp. nov. (♀), Sonoita ledouxi sp. nov. (♂♀), Sphericula globulifera gen. et sp. nov. (♀), Thiratoscirtus silvestris sp. nov. (♂♀), Tusitala bandama sp. nov. (♀) and Tusitala cornuta sp. nov. (♂). Five specific names are synonymized: Polemus chrysochirus Simon, 1902 with Baryphas jullieni Simon, 1902, Viciria mondoni Berland & Millot, 1941with Malloneta guineensis Simon, 1902, Brancus lacrimosus Wesołowska & Edwards 2008 with Vicirionessa fuscimana (Simon, 1903), Viciria monodi Berland & Millot, 1941 and Viciria equestris pallida Berland & Millot, 1941 with Vicirionessa equestris (Simon, 1903). Hyllus natali peckhamorum Berland & Millot, 1941 is removed from synonymy of Hyllus brevitarsis Simon, 1902, revalidated and its rank is raised as Hyllus peckhamorum Berland & Millot, 1941 stat. nov. Also rank of Telamonia aequipes minor Lessert, 1925 is elevated as Phintella minor (Lessert, 1925) stat. nov. Menemerus dubius Berland & Millot, 1941 is removed from nomina dubia. This species is considered valid and is redescribed. A lectotype is designated for it. The male of Mexcala torquata Wesołowska, 2009 and females of Hyllus tuberculatus Wanless & Clark, 1975, Iranattus principalis (Wesołowska, 2000), Myrmarachne eidmanni Roewer, 1942 and Thiratoscirtus tentativus (Szűts & Jocqué, 2001) are described for the first time. Many new combinations are proposed. Twenty ex Brancus are recombined: Hyllus nigeriensis (Wesołowska & Edwards, 2012) comb. nov., Thyene blaisei (Simon, 1902) comb. nov., Thyene calebi (Kanesharatnam & Benjamin, 2018) comb. nov., Thyene mutica (Simon, 1902) comb. nov., Thyene verdieri (Berland & Millot, 1941) comb. nov., Vicirionessa besanconi (Berland & Millot, 1941) gen. et comb. nov., Vicirionessa fuscimana (Simon, 1903) gen. et comb. nov., Vicirionessa mustela (Simon, 1902) gen. et comb. nov., Vicirionessa niveimana (Simon, 1902) gen. et comb. nov., Vicirionessa occidentalis (Wesołowska & Russell-Smith, 2011) gen. et comb. nov., Vicirionessa peckhamorum (Lessert, 1927) gen. et comb. nov., Vicirionessa signata (Dawidowicz & Wesołowska, 2016) gen. et comb. nov. Four ex Viciria are recombined: Vicirionessa chabanaudi (Fage, 1923) gen. et comb. nov., Vicirionessa equestris (Simon, 1903) gen. et comb. nov., Vicirionessa prenanti (Berland & Millot, 1941) gen. et comb. nov., Vicirionessa tergina (Simon, 1903) gen. et comb. nov. and one species ex Hyllus: Vicirionessa albocincta (Thorell, 1899) gen. et comb. nov. Furthermore, the following two new combinations are proposed: Thiratoscirtus tentativus (Szűts & Jocqué, 2001) comb. nov. (ex Bacelarella) and Baryphas galeatus (Simon, 1902) comb. nov. (ex Polemus). For 11 species known so far from single records new data are presented: Heliophanus butemboensis Wesołowska, 1986, Hyllus lwoffi Berland & Millot, 1941, Hyllus tuberculatus Wanless & Clark, 1975, Menemerus dubius Berland & Millot, 1941, Mexcala torquata Wesołowska, 2009, Neaetha maxima Wesołowska & Russell-Smith, 2011, Pachyballus miniscutulus Wesołowska, Azarkina & Wiśniewski 2020, Phintella paludosa Wesołowska & Edwards, 2012, Thiratoscirtus gambari Wesołowska & Russell-Smith, 2011, Tusitala guineensis Berland & Millot, 1941 and Tusitala lutzi Lessert, 1927.